The American Evangelical Christians and the U.S. Middle East policy: A case study of the Christians United for Israel (CUFI) - Salleh, Mohd Affandi; Zakariya, Hafiz (IIUM Press, 2012)
This study examines the relationship between religious belief and interest group activism in influencing American foreign policy making by highlighting a group within the American Evangelical Christians namely, Christians United for Israel (CUFI). At present, the organisation is actively involved in lobbying for influence over American foreign policy towards the Middle East in general and Israel in particular. It explores the background and strategies of CUFI, by discussing how its underpinning religious beliefs – notably Eschatology and attitude towards End Time - provide the basis of support for the state of Israel. This study contends that the activism of the organisation demonstrates how religious beliefs can constitute a strong factor in motivating lobbying activity in the US foreign policy which could give potential impact on US foreign policy making.